Connections of the mediodorsal nucleus of the thalamus in the tree shrew. II. Efferent connections. - Divac, I; Passingham, R (1980)
[35S]Methionine was injected into the mediodorsal nucleus of the thalamus of 5 adult tree shrews (Tupaia belangeri) and into the medioventral thalamic nucleus in another tree shrew. Three animals survived for 44 h and three others for two weeks (including the animal with the injection in the medioventral nucleus). Contact autoradiograms were made on an X-ray film. The mediodorsal thalamic nucleus was found to project ipsilaterally to all surfaces of the frontal pole of the cerebral cortex. No other projections of this nucleus have been established. Also in this species, the medioventral nucleus projects to the first layer of the entire neocortex ipsilaterally and to the mesencephalic tegmentum.